2009
DOI: 10.1073/pnas.0905811106
|View full text |Cite
|
Sign up to set email alerts
|

Functional interaction between native G protein-coupled purinergic receptors in Xenopus follicles

Abstract: Purinergic receptors are expressed in the membrane of the follicular cell layer that communicates with the Xenopus oocyte. Adenosine (Ado) generates a cAMP-dependent K ؉ current (IK,cAMP), whereas ATP activates a Cl ؊ current (FCl) and has a dual effect on I K,cAMP, provoking both its activation and inhibition. Here, purinergic responses were studied electrophysiologically, first in the whole follicle (w.f.), and then in the same follicle after removal of its epithelium/theca layers (e.t.r. follicle). Response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Matzuk et al 2002), whereas others were suggested based on their conspicuous expression and actions in ovarian systems of numerous species. The latter is the case for purinergic signalling, which has been demonstrated to be functionally expressed in ovarian cells of several vertebrates (Arellano et al 1998(Arellano et al , 2002(Arellano et al , 2009(Arellano et al , 2011Vázquez-Cuevas et al 2006Bintig et al 2009). Purinergic signalling is now known to be an important paracrine regulator in distinct cell systems, both in physiological and pathological processes (Burnstock 2007;Corriden and Insel 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matzuk et al 2002), whereas others were suggested based on their conspicuous expression and actions in ovarian systems of numerous species. The latter is the case for purinergic signalling, which has been demonstrated to be functionally expressed in ovarian cells of several vertebrates (Arellano et al 1998(Arellano et al , 2002(Arellano et al , 2009(Arellano et al , 2011Vázquez-Cuevas et al 2006Bintig et al 2009). Purinergic signalling is now known to be an important paracrine regulator in distinct cell systems, both in physiological and pathological processes (Burnstock 2007;Corriden and Insel 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A role for purinergic signalling in ovarian function has been proposed (Arellano et al 1998(Arellano et al , 2002(Arellano et al , 2009(Arellano et al , 2011Vázquez-Cuevas et al 2006Bintig et al 2009). Purinergic signalling by ATP and its hydrolysis products is now recognised as a paracrine/autocrine system that has a role in many physiological phenomena, acting on a variety of cell types (Burnstock 2007;Corriden and Insel 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Since UTP and ATP are equipotent, this effect could be mediated by a P2Y 2 or P2Y 4 receptor subtype [136]. Moreover, it has been suggested that there are close interactions between A 2 and P2Y receptors in Xenopus follicles [19]. Cultured CHO cells express a P2 receptor equi-reactive to ATP and UTP [178], probably the P2Y 2 and/or P2Y 4 subtype.…”
Section: Female Reproductive Organsmentioning
confidence: 99%
“…,b, Arellano et al . , , ). Defolliculated oocytes are reputed to express a few if any purinergic receptors, and this was based on the observation that ATP failed to activate current responses.…”
Section: Discussionmentioning
confidence: 99%